HANDLING UNEMPLOYMENT IN INDONESIA - Nurrahman, Agung (Registratie, 2024)
This study aims to identify studies that reflect the trend of a series of publications related to unemployment issues in Indonesia and describe them visually. This research method uses visualization methods and bibliometric analysis. The results showed that the item with the most occurrences is "Indonesia" with 221 occurrences and followed by "Unemployment" with 145 occurrences. The topics that are still rarely discussed include human development index, income inequality, human capital, investment, inflation, labor market, economic growth, occupation, knowledge, social stigma, social support, health care delivery, urbanization, rural population, and risk factors. The next research has the opportunity to use these topics as research objects, especially by analyzing the relationship / relationship with the handling of unemployment in Indonesia. There are also 5 categorizations of unemployment handling efforts in Indonesia based on the content of 51 research publications, including: provision of quality work, increased work productivity, entrepreneurship education in universities, Indonesian moter policy and labor market policy. In conclusion, bibliometric research related to unemployment in Indonesia using the Scopus database provides an overview of publication trends, dominant keywords, and topics that have not been widely discussed. There is potential for further research with a focus on topics that are rarely discussed, as well as their relevance to efforts to address unemployment in Indonesia, as found in the categories of efforts identified from these research publications.